1994
DOI: 10.1172/jci117237
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme replacement therapy for murine mucopolysaccharidosis type VII.

Abstract: Recombinant mouse el-glucuronidase administered intravenously to newborn mice with mucopolysaccharidosis type VII (MPS VII) is rapidly cleared from the circulation and localized in many tissues. Here we determine the tissue distribution of injected enzyme and describe its effects on the histopathology in 6-wk-old MPS VII mice that received either one injection of 28,000 U recombinant 5-glucuronidase at 5 wk of age or received six injections of 28,000 U given at weekly intervals beginning at birth. These mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
138
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 196 publications
(145 citation statements)
references
References 31 publications
6
138
1
Order By: Relevance
“…Although not quantified, persistent GUSB activity was also seen in the retinal pigmented epithelium by histochemical staining (data not shown). Levels of GUSB activity greater than 1-5% normal have previously been shown to be sufficient to correct histopathologic disease in many tissues, 6,9,18 and tissue sections from 1-year-old animals in this study showed a marked reduction of lysosomal storage similar to that previously described 17 (data not shown). Persistence of transduced cDNA was documented by PCR in most tissues at 1 year of age ( Figure 2), with the notable exception of the spleen, suggesting that the persistence of splenic GUSB activity is primarily due to cross-correction.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Although not quantified, persistent GUSB activity was also seen in the retinal pigmented epithelium by histochemical staining (data not shown). Levels of GUSB activity greater than 1-5% normal have previously been shown to be sufficient to correct histopathologic disease in many tissues, 6,9,18 and tissue sections from 1-year-old animals in this study showed a marked reduction of lysosomal storage similar to that previously described 17 (data not shown). Persistence of transduced cDNA was documented by PCR in most tissues at 1 year of age ( Figure 2), with the notable exception of the spleen, suggesting that the persistence of splenic GUSB activity is primarily due to cross-correction.…”
Section: Resultssupporting
confidence: 87%
“…High levels of GUSB are initially achieved in most tissues following ERT, leading to reversal of lysosomal distention and improvements in higher mental and auditory functions. [8][9][10] However, this effect is transient, and as the infused GUSB activity decreases lysosomal distention will recur. 11 To provide a more persistent source of GUSB activity, BMT using syngeneic GUSB-positive bone marrow has been examined.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations